Firefighter commenting on prototype firefighter uniform design - Eisele, John, photographer (Colorado State University. Libraries, 2016)
Joe Leste, Battalion Chief Fairmount Fire Protection District, Golden, Colorado (left) Tyler Rooney (center) Elliot Glik (right).
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards